2014
DOI: 10.9745/ghsp-d-13-00116
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up delivery of contraceptive implants in sub-Saharan Africa: operational experiences of Marie Stopes International

Abstract: Between 2008 and 2012, Marie Stopes International (MSI) provided 1.7 million contraceptive implants in sub-Saharan Africa as part of a comprehensive method mix, primarily through mobile outreach using dedicated MSI providers and also through social franchising and MSI-run clinics. Large-scale access, quality, and informed choice were key elements of MSI's strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 18 publications
5
104
0
Order By: Relevance
“…[9] These efforts boosted the confidence of providers to remove implants; at follow-up, none of those trained had refused to do removals, an issue which had previously hampered the programme. [9] All the nurses expressed enthusiasm about the prospect of attending further training by qualified personnel. Opportunities for practical experience, where several insertions and removals are done under supervision, and for continued mentoring, appear to be particularly important, with nurse E saying: 'It just needs some practice.…”
Section: Key Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[9] These efforts boosted the confidence of providers to remove implants; at follow-up, none of those trained had refused to do removals, an issue which had previously hampered the programme. [9] All the nurses expressed enthusiasm about the prospect of attending further training by qualified personnel. Opportunities for practical experience, where several insertions and removals are done under supervision, and for continued mentoring, appear to be particularly important, with nurse E saying: 'It just needs some practice.…”
Section: Key Findings and Discussionmentioning
confidence: 99%
“…Consistent with this, several studies on implant services in a range of settings have shown that providers' level of knowledge, especially around counselling, is a key determinant of the uptake of the implant and subsequent continuation. [9,15,18,20] Of note, a study across several sub-Saharan African countries showed the benefits of competency-based training on the implant, sideeffect management, and regular mandatory refresher courses and mentorship. [9] These efforts boosted the confidence of providers to remove implants; at follow-up, none of those trained had refused to do removals, an issue which had previously hampered the programme.…”
Section: Key Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22] Equally, the voices of satisfied clients, who comprise the large majority of women who insert the implant, must be allowed to shape the public discourse about the method. [23] Even though few women cited pamphlets, television or social media as direct sources of information about the implant, these media could play an important role in reinforcing the testimonies of women who are satisfied with the method, and in counteracting negative perceptions and rumours before these become entrenched. Demand-creation efforts around the time of introducing the implant in SA, successfully generated positive impressions of the method.…”
Section: Misconceptions and Demand Creationmentioning
confidence: 99%